Mechanical/Electrical Hybrid Two-Dimensional Beam Scanning Cylindrical Dielectric Lens Antenna Fed by a Phased Array Primary Radiator - Yoshiki Sugimoto; Kunio Sakakibara; Tuan Hung Nguyen; Takanori Narita; Nobuyoshi Kikuma (IEEE Access)
A hybrid two-dimensional (2D) beam-scanning lens antenna through the combination of a mechanical lens slide and a phased array primary radiator is proposed. The proposed antenna allowed for mechanical scanning of the main beam in one dimension by utilizing a piezo motor to slide the lens, while also enabling electrical scanning of the beam through a phased array of primary radiators arranged orthogonal to the mechanical beam scanning direction. The effectiveness of the proposed antenna was demonstrated through electromagnetic simulations and fabricated antenna measurements. We have shown the capability of the proposed antenna to perform 2D beam scanning with a scan loss of approximately 3 dB over a spherical angular range of ±10° from the front direction of the antenna.